Sequence diversity and associated pathogenicity of the hemagglutinin cleavage site of H5N2 avian influenza viruses isolated from chickens in Taiwan during 2013–2015 - LI, Kuang-Po; CHANG, Poa-Chun; CHENG, Ming-Chu; TAN, Duen-Huey; CHEN, Li-Hsuan; LIU, Yu-Pin; LIN, Yu-Ju; TSAI, Hsiang-Jung; SHIEN, Jui-Hung (Journal of Veterinary Medical Science, 2017)
The sequence at the hemagglutinin (HA) cleavage site (CS) plays a key role in determining the pathogenicity of avian influenza viruses. Three types of HA CS sequences, QREKR/GL, QRKKR/GL and QRRKR/GL, were previously reported in Taiwanese H5N2 viruses that were isolated from chickens from 2003 to 2013. However, no HA CS sequence was reported for viruses isolated after 2013. This article presents the HA CS sequences and pathogenicity of H5N2 viruses that were isolated from chickens in Taiwan during 2013–2015. Two novel HA CS sequences, QKEKR/GL and KREKREKR/GL, were found in the viruses isolated in 2013 and 2014, and pathogenicity tests showed that the viruses with these novel HA CS sequences are low and high pathogenic viruses, respectively. In contrast, the HA CS sequence QREKR/GL was found in all viruses that were isolated in 2015, and all of these viruses were low pathogenic viruses. After 10 passages in embryonated chicken eggs, a virus strain that was isolated in 2003 evolved into a viral quasispecies that contained at least four distinct types of HA CS sequences. These results highlight the potential of Taiwanese H5N2 viruses to change their pathogenicity and HA CS sequences via mutations. Furthermore, viruses with the HA CS sequence QREKR/GL were more prevalent than others in 2015. These findings are useful for understanding the mechanism of sequence changes at the HA CS and for refining H5N2 virus control measures in Taiwan.